The Meaning of Sustainability in Business Strategy: An Interpretive Approach to the Integration of Social and Profit Values in Modern Management (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2025)
This study explores how Generation Z constructs work values and meaning in modern organizations shaped by digitalization and social transformation. Using a qualitative phenomenological approach under a social constructivist paradigm, the research investigates the lived experiences of young professionals in the digital, creative, and startup sectors. Data were collected through in-depth interviews and non-participant observation and analyzed using thematic analysis (Braun & Clarke, 2006; Moustakas, 1994). Findings show that Generation Z defines work through three interrelated dimensions: (1) intrinsic motivation grounded in personal purpose and self-expression, (2) redefined productivity emphasizing creativity and emotional balance rather than quantitative output, and (3) job satisfaction derived from inclusive culture and adaptive leadership. These results support Self-Determination Theory (Deci & Ryan, 2000) and Social Constructionism (Berger & Luckmann, 1966), showing that work meaning is socially constructed rather than objectively given. Overall, the study concludes that for Generation Z, work represents not merely economic activity but a medium for identity, contribution, and personal growth, urging organizations to embrace meaning-centered and value-driven leadership to enhance engagement and fulfillment.